DESAFIOS DE LA EDUCACION EN EL FUTURO DE LA UNIVERSIDAD - Fairlie Frisancho, Ebor (2007)
The present article gathers some opinions about that we can expect of the education in a perhaps not so distant future, at least in Latin America and Spain. The opinions are of researches of universities, who they analyze the objectives, challenges, investment, culture and strategies. The role of the World Bank is imponderable for the improvement of the studies and diverse alternatives are presented to take into account and to enter to the challenge to improve the education in the higher education institutions in agreement with the standards of quality established by the countries developed